INCIDENCE, PROPHYLAXIS AND TREATMENT PRINCIPLES OF PRIMARY TEETH EROSION IN CHILDREN - Akhmedov, A.B.; Gafforov, S.A.; Ishanova, M.K.; Gafforova, S.S. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
We conducted a retrospective analysis of children aged 2-5 years (495 patients). We used the O’Sullivan index to measure erosion of deciduous teeth. The prevalence of tooth erosion in children aged 2–5 years was 29.9% (95% confidence interval – 24.4-35.4). For treatment, a fluocal gel (Fluocal gel, Fluocal solution, Septodont), a solution of calcium gluconate for injection (10%), ROKS gel (ROCS® Medical Minerals) were used. Biologically active substances (Fuji-IX, GC), arget (VladMiVa) were used. The basic principles of prevention and treatment of erosion of deciduous teeth in children. Based on the information presented in the article, it is concluded that the problem is serious enough, that there is a need for further prevention of this pathology and the need to develop modern treatment methods.